European Congress of Mathematics 2001
DOI: 10.1007/978-3-0348-8266-8_45
|View full text |Cite
|
Sign up to set email alerts
|

New Invariants of Legendrian Knots

Abstract: We present two different constructions of invariants for Legendrian knots in the standard contact space R 3 . These invariants are defined combinatorially, in terms of certain planar projections, and are useful in distinguishing Legendrian knots that have the same classical invariants but are not Legendrian isotopic.2000 Mathematics Subject Classification: 57R17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The space of such knots, modulo reparametrization, is denoted by Leg(S 1 , R 3 ). We will refer to connected components of Leg(S 1 , R 3 ) (with respect to the quotient of the C ∞ topology) as Legendrian knot types 5 . When talking about classical or smooth knots, we simply mean that the Legendrian assumption is not made.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The space of such knots, modulo reparametrization, is denoted by Leg(S 1 , R 3 ). We will refer to connected components of Leg(S 1 , R 3 ) (with respect to the quotient of the C ∞ topology) as Legendrian knot types 5 . When talking about classical or smooth knots, we simply mean that the Legendrian assumption is not made.…”
Section: Preliminariesmentioning
confidence: 99%
“…Such a diagram always has an admissible decomposition (or ruling) in the sense of [5]: the only two values of the Maslov potential (even though it's Z-valued) are 1 on the upper strands and 0 on the strands of the original braid β , thus all crossings are Maslov, and we may declare all of them switching (in the multi-component case, consider only proper crossings). This gives rise to a decomposition where the discs are nested in one another, so it's admissible.…”
Section: Remark 73mentioning
confidence: 99%
See 1 more Smart Citation
“…Chekanov [3] and Eliashberg [7] showed that there exist formally Legendrian isotopic knots in R 2 × R which are not Legendrian isotopic using Legendrian contact homology. Legendrian contact homology associates a differential graded algebra (DGA) to a Legendrian knot K. The DGA is generated by Reeb chords on K, that is, flow lines of R starting and ending on K and the differential is given by a holomorphic curve count in the symplectization of the contact manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning in the late 1990's, two nonclassical invariants of such Legendrian knots emerged. The first is based on the contact homology theory of Eliashberg and Hofer [Eliashberg 1998], and was couched in combinatorial form by Chekanov [2002a]. This invariant is a differential graded algebra that counts certain holomorphic disks in the symplectization of ‫ޒ‬ 3 .…”
Section: Introductionmentioning
confidence: 99%